Enter the Structures of the Indonesian Language in the Writing of the Arabic Language/تدخل تراكيب اللغة الإندونيسية في كتابة اللغة العربية - Ad-Din, Ahmar (Nurul Jadid University, 2017)
Communication ability among nations forces every individual person to master arabic language. In the teaching learning proces, university students face a problem. They bring their native language structure indonesia into arabic study. This causes several mistakes toward the learnt language. Therfore, an immediate solving problem is needed to solve the problem. Until arabic language can be for away from mistakes.This research wants to know and find the lenguage mistakes, causes and solutins. While the reasearch uses the several ways. Those are : interview, observation and documentation. The research result shous language mistakes causes by several factors. Those are : misunderstanding of language rules. A seldom practice intervention betwen those language (arabic-indonesia).القدرة عل التواصل بين أبناء دول العالم دفعت كل واحد منهم إلى تعلم اللغة العربية ومعرفتها وممارستها. ولكن في العملية التعليمية قابل الطلبة صعوبة ومشكلة حيث حملوا أنماط اللغة الأم الى اللغة المدروسة. وترتب هذا التدخل اللغوي إلى فساد اللغة الهدف. لذا، من المفروض أن يكون هناك أي محاولة لتصويب هذه المشكلة اللغوية من أجل حفظ اللغة الثانية العربية. وقد قصد الباحث بهذا البحث أن يتعرف إلى الاخطاء والعوامل المؤثرة على وقوع الأخطاء وتقديم العلاج لهذه الاخطاء. وأجريت الدراسة بأدوات التالية: هي المقابلة والملاحظة وجمع الوثائق للحصول على الإجابة العلمية، ونتائجها كما سياتي: الجهل بقيود اللغة العربية وقلة الممارسة والتدخل اللغوي بين كلتا للغوتين العربية والإندونسية.واختتم الباحث بحل أن يتدرب الطلبة على الانشاء تدربا مستمرا باستخدام اي شكل إنشائي حتى اتعودوا على كتابة اللغة العربية الصحيحة الفصيحة.